Sistema FiWi 6G Baseado em FSO, RoF e VLC - Lopes , Celso Henrique (2023)
This work presents solutions of hybrid optical network architectures to be employed in fifth (5G, fifth-generation) and sixth (6G, sixth-generation) generation wireless networks. By adopting the 5G New Radio (NR) standard, along with photonic techniques for frequency multiplication, optical fiber infrastructure, millimeter wave communications, free-space optical transmission (FSO), and visible light communication (VLC), we were able to experimentally implement the proposed network and evaluate the performance of the architectures based on the specifications of the 3rd Generation Partnership Project (3GPP) Release 18. The first contribution consists of applying the photonic technique (CS-DSB, carrier suppressed double side band) in passive network systems with wavelength-division multiplexing (WDM-PON, wavelength-division multiplexing passive optical network) for transmitting 5G NR signals at a frequency of 60 GHz. Through the use of cascaded electro-optic modulators, it was possible to generate and transmit the 5G NR signal in the V band, proposed by 3GPP Release 18, achieving a data throughput of 11.8 Gbit/s. The second contribution addresses a hybrid system that combines analog radio over fiber (A-RoF) and FSO to enhance the fronthaul of the network, while a dual access proposal using VLC and millimeter waves was implemented. This architecture was designed to meet the demands of mobile communications in both indoor and outdoor environments, with the ability to achieve speeds of up to 4.92 Gbit/s. In summary, this study illustrates the enormous potential of hybrid optical networks in implifying wireless communication in state-of-the-art cellular networks. The contributions offered not only demonstrate the feasibility of these approaches but also promise applicability in a variety of scenarios, covering indoor and outdoor environments.